(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics and evaluate the outcomes of care for patients with non-small cell lung cancer (NSCLC) receiving adjuvant chemotherapy after surgery at K Hospital. Subjects and Methods: A descriptive study was conducted on 126 NSCLC patients undergoing adjuvant chemotherapy from March 2024 to August 2024 at K Hospital. Patients were assessed for symptom improvement, management of adverse effects, and satisfaction with nursing care. Results: The mean age was 62.4±9.2 years, with males accounting for 67.4%. The proportion of patients with a smoking history was 62.7%. Carboplatin-containing regimens were the most commonly used (60.3%). Common clinical symptoms included dry cough (73.8%), chest pain (46.8%), and dyspnea (29.4%). The main adverse effects were fatigue (49.5%), nausea and vomiting (47.6%), and neutropenia (45.2%). The symptom improvement rate exceeded 90%. The improvement rates for adverse effects such as fatigue, nausea, vomiting, diarrhea, constipation, neutropenia, and thrombocytopenia reached 100%. The proportion of patients receiving appropriate chemotherapy administration procedures, care, and counseling during and after chemotherapy exceeded 90%. The proportion of patients receiving psychological support and lifestyle guidance also exceeded 90%. The satisfaction rate with nursing care was 98.4%. Conclusion: Nursing care plays an important role in improving symptoms, managing adverse effects, and enhancing treatment outcomes for NSCLC patients undergoing adjuvant chemotherapy after surgery.